Second Link : Viewpoints on Video in the Eighties. - Barling, Marion; Doyle, Helen; Falk, Lorne; Gale, Peggy; Huffman, Kathy; Loeffler, Carl E.; London, Barbara; MacNevin, Brian; Mignot, Dorine; Murray, Ian; Nairne, Sandy; Slopek, Edward; et al. (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1983)
Abramovic, Marina & Ulay ; Bódy, Gabor ; Byrne, James ; Casinière, Joëlle de la ; Frenkel, Vera ; Hill, Gary ; Memory of your nose ; Oursler, Tony ; Steele, Lisa ; Veeder, Jane ; Hawley, Steve ; Steyger, Tony ; Almy, Max ; Bourn, Ian ; Cohn, Norman ; Geller, Matthew ; Keane, Tina ; Lucier, Mary ; Scarlett-Davis, John ; Struycken, Peter ; Viola, Bill ; Metcalfe, Eric ; Atchley, Dana ; Barling, Marion ; Bruch, Klaus vom ; Doyle, Helen ; General Idea ; Labat, Tony ; Murray, Ian ; Slopek, Ed ; Sturgeon, John ; Watt, John
videotapes, selected screenings, selected exhibitions, bibliography 1 p.
Engels
The second link : viewpoints on video in the eighties, Walter Phillips Gallery - The Banff Centre for the Arts Banff, July 8-21, 1983
kunstcatalogus
Keywords: jaren 80